The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/02770903.2017.1337787
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for asthma among adults exposed to the September 11, 2001 World Trade Center terrorist attack

Abstract: Objective: We described the patterns of asthma hospitalization among persons exposed to the 2001 World Trade Center (WTC) attacks, and assessed whether 9/11-related exposures or comorbidities, including posttraumatic stress disorder (PTSD) and gastroesophageal reflux symptoms (GERS), were associated with an increased rate of hospitalization. Methods: Data for adult enrollees in the WTC Health Registry, a prospective cohort study, with self-reported physician-diagnosed asthma who resided in New York State on 9/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…We found that demographic characteristics, themselves proxies for structural racism, known to be risk factors for either self-reported disease and/or hospitalization for physical health conditions of interest, such as asthma, GERDS, cardiovascular disease, including race/ethnicity and socioeconomic status, were significantly associated with hospitalization for a 9/11-related physical health condition [ 33 , 34 , 35 ]. Our findings align with previous 9/11 research showing that both minority children and adults and those from low SES backgrounds were at higher risk of asthma [ 2 , 3 , 23 ]. In addition, a previous study found that children from lower income households were more likely to have uncontrolled asthma [ 4 ], which could lead to ED visits.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that demographic characteristics, themselves proxies for structural racism, known to be risk factors for either self-reported disease and/or hospitalization for physical health conditions of interest, such as asthma, GERDS, cardiovascular disease, including race/ethnicity and socioeconomic status, were significantly associated with hospitalization for a 9/11-related physical health condition [ 33 , 34 , 35 ]. Our findings align with previous 9/11 research showing that both minority children and adults and those from low SES backgrounds were at higher risk of asthma [ 2 , 3 , 23 ]. In addition, a previous study found that children from lower income households were more likely to have uncontrolled asthma [ 4 ], which could lead to ED visits.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies among adults and children exposed to 9/11 identified a relationship between dust exposure and asthma [ 2 , 3 , 4 , 30 , 31 ]. However, a study among 9/11-exposed adults did not find an association between asthma hospitalization and dust cloud [ 23 ]. Previous research on self-reported asthma control among 9/11-exposed adults and children found that dust cloud exposure was not associated with the level of asthma control [ 4 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis builds on previous work on this topic by using additional data through 2016 and also formally testing whether barriers to care mediate the association between SES and asthma hospitalizations. 4 It is also the first study, to our knowledge, to explicitly examine these pathways in a disaster-exposed population with elevated rates of respiratory illness. 9 their health conditions before and after 9/11.…”
Section: Introductionmentioning
confidence: 99%